An Indonesian Adaptation of the World Health Organization Adverse Childhood Experiences International Questionnaire (WHO ACE-IQ) as a Screening Instrument for Adults - Satwika Rahapsari; Valendra Granitha Shandika Puri; Adelia Khrisna Putri (Gadjah Mada Journal of Psychology (GamaJoP), 2021)
There has been little research in Indonesia about Adverse Childhood Experiences (ACE). Whereas, research on this topic is urgently needed as the baseline for a national evidence-based child protection policy. Even though the worldwide prevalence of ACE is high, there is no comprehensive study in the Indonesian context in regards to ACE identification and the impact on the survivors’ mental and physical health. Therefore, an ACE screening instrument is urgently needed as the first step for conducting research on this topic. This research aims to examine the validity and reliability of the WHO ACE-IQ or the World Health Organization Adverse Childhood Experience International Questionnaire as an ACE screening instrument in Indonesia. The researcher conducted a cross-sectional survey in 240 participants aged 18-65 years old using an online self-administered questionnaire. The outcome of this research is the Indonesian adapted WHO ACE-IQ is able to provide a reliable, accurate, and valid score of ACE in the Indonesian adult population